2012
DOI: 10.2337/db11-1753
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Differences in Adipocyte Precursor Cells From Different White Fat Depots

Abstract: Obesity and body fat distribution are important risk factors for the development of type 2 diabetes and metabolic syndrome. Evidence has accumulated that this risk is related to intrinsic differences in behavior of adipocytes in different fat depots. In the current study, we demonstrate that adipocyte precursor cells (APCs) isolated from visceral and subcutaneous white adipose depots of mice have distinct patterns of gene expression, differentiation potential, and response to environmental and genetic influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
261
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(287 citation statements)
references
References 35 publications
20
261
2
4
Order By: Relevance
“…In general, across studies, SAT adipocytes were significantly larger than VAT adipocytes, irrespective of BMI or metabolic state (Liu et al, 2009;Tchernof et al, 2006), suggesting that SAT undergoes greater hypertrophy relative to VAT. However, previous studies have suggested that SAT is inherently more hyperplastic than VAT, although these observations were based on in vitro data from mouse and humans showing that SAT-derived cells have greater adipogenic capacity than VAT-derived cells (Baglioni et al, 2012;Macotela et al, 2012;Tchkonia et al, 2006). More recent in vivo data, from the transgenic AdipoChaser mouse line, have suggested the opposite: following diet-induced obesity, VAT (epidydimal) underwent waves of hyperplastic growth, whereas SAT (inguinal) did not .…”
Section: Regional Variation In Adipose Morphologymentioning
confidence: 69%
“…In general, across studies, SAT adipocytes were significantly larger than VAT adipocytes, irrespective of BMI or metabolic state (Liu et al, 2009;Tchernof et al, 2006), suggesting that SAT undergoes greater hypertrophy relative to VAT. However, previous studies have suggested that SAT is inherently more hyperplastic than VAT, although these observations were based on in vitro data from mouse and humans showing that SAT-derived cells have greater adipogenic capacity than VAT-derived cells (Baglioni et al, 2012;Macotela et al, 2012;Tchkonia et al, 2006). More recent in vivo data, from the transgenic AdipoChaser mouse line, have suggested the opposite: following diet-induced obesity, VAT (epidydimal) underwent waves of hyperplastic growth, whereas SAT (inguinal) did not .…”
Section: Regional Variation In Adipose Morphologymentioning
confidence: 69%
“…29 WAT is found in both subcutaneous and visceral depots, and increased visceral WAT mass is associated with increased metabolic risk. 32,33 WAT has important endocrine and paracrine roles throughout the body, 29,34,35 and in general terms, functions to store energy, mainly in the form of triglycerides. 36,37 In contrast to WAT, brown adipose tissue (BAT) primarily functions to expend energy.…”
Section: 31mentioning
confidence: 99%
“…[46][47][48][49] The second line of research is the recognition of the tremendous heterogeneity of adipocytes throughout the body with regard to cellular origins and metabolic plasticity. [50][51][52] This new research raises the hope that one might target the intrinsic cellular and metabolic plasticity of adipocytes and adipocyte progenitors for therapeutic benefit. These are clearly early days, and it may be useful to reflect on how conclusions from the first wave of BAT research might be integrated to advance the exciting new era.…”
Section: The Central Role Of Bat In Nonshivering Thermogenesis and Tmentioning
confidence: 99%
“…40,52,60 As detailed in the following papers, work by Kajimura has demonstrated the importance of PRDM16 in specifying the brown fat lineage, including the central role of EMH1. [61][62][63] Work from the Tseng laboratory was among the first to establish the cellular complexity of cells capable of uncoupling protein-1 expression, 51 including the critical role of BMP7 signaling in classic and inducible brown adipogenesis. [64][65][66] Each of these discoveries has provided new insights and tools for assessing brown fat function.…”
Section: The Central Role Of Bat In Nonshivering Thermogenesis and Tmentioning
confidence: 99%